ENHANCING ACCOUNTABILITY AND TRANSPARENCY IN LOCAL GOVERNANCE THROUGH INTEGRATED INFORMATION SYSTEMS: A CASE STUDY OF SURABAYA CITY, INDONESIA - Hidayat, Muhammad Nurdin (Alqaprint Jatinangor, 2024)
This study explores how integrated information systems enhance accountability and transparency in local governance, focusing on the case of Surabaya City, Indonesia. As public demands for open and efficient administration increase, local governments are under pressure to adopt digital tools that support transparent decision-making and accessible public services. This research adopts a literature review method, systematically analyzing scholarly sources published in the last decade related to digital governance, e-government, and information system integration. Findings indicate that the implementation of integrated information systems contributes significantly to reducing bureaucratic opacity and improving public trust. Surabaya City has emerged as a national model due to its progressive use of digital platforms to promote real-time data sharing and citizen engagement. Key enabling factors include strong political leadership, cross-sectoral collaboration, and investment in digital infrastructure. However, challenges remain in ensuring data interoperability, cybersecurity, and capacity building among public servants. The study highlights critical insights from both domestic and international experiences, offering a comparative lens for analysis. By synthesizing existing literature, this research provides a conceptual foundation for policymakers seeking to enhance local governance through technology. The findings underscore the need for a comprehensive and adaptive strategy to sustain digital transformation in the public sector.